PENGARUH CORPORATE SOCIAL RENSPONBLITIY (CSR) TERHADAP NILAI PERUSAHAAN PADA BANK BRI CABANG PAREPARE - Darmawan, Darmawan; Ikbal, Muh (Universitas Muhammadiyah Parepare, 2019)
This type of research is classified as quantitative research. The study population was all 100 CSR traders registered in the Pare Beach area. The sampling technique is purposive sampling. The sample of this research is 50 companies. Data analysis with simple regression. The results of this study concluded that. Based on the results of tests conducted by t test the variable of corporate social responsibility significantly influence the variable value of the company as much as 60 percent. Then the coefficient of determination (R Square) of 0.600. This means that 60% of the company value variable can be explained by the independent variable, namely CSR, while the rest (100% - 60% = 40%) is explained by other causes outside the model.